Integrated Sociotechnical Package for Soil Restoration in El Rhahla Landscape, Central West Tunisia - Idoudi, Zied; Rudiger, Udo; Frija, Aymen (International Center for Agricultural Research in the Dry Areas, 2022)
“Integrated Sociotechnical Package for Soil Restoration in El Rhahla Landscape, Central West Tunisia” is a short movie documenting the ICARDA approaches and interventions related to the sociotechnical bundle of innovation undertaken by the ICARDA-GIZ ProSol Global Program in collaboration with the CGIAR initiative on Agroecology in El Rhahla region (Siliana District) as part of the Tunisian Agroecological Living Landscape – it also presents a series of testimonies on (i) the challenges farmers are facing, (ii) the solutions brought to face these challenges and (iii) how these solutions can improve the livelihood of famers in the crop-livestock farming system.